Odpowiedzi

2009-11-27T19:55:11+01:00
A/(k-0,5l)(k+6)+k²=k²+6k-0,5kl-3l+k²=2k²+6k-0,5kl-3l

b/(c-1,5c)(12+c)-c²=c²+12c-18c-1,5c²=-0,5c²-6c

c/ (2a-b)(a-2b)+5a²=2a²-4ab-ba+2b²+5a²=7a²-5ab+2b²

d/ (b-4)(b-3)-b(b+3)=b²-3b-4b+12-b²-3b=-10b+12

e/ -(a-b)-5(a-2)(b+1)=-a+b-5(ab+a-2b-2)=
=-a+b-5ab-5a+10b+10=-6a+11b-5ab+10

f/ x(y+2)+(3x+4-y)(y+4)=xy+2y+3xy+12x+4y+16-y²-4y=
=4xy+2y+12x+16
1 1 1
2009-11-27T20:05:20+01:00
A/(k-0,5l)(k+6)+k²=k²-0,5lk+6k-3l+k²=2k²-0,5lk+6k-3l
b/(c-1,5c)(12+c)-c²=-0,5c(12+c)-c²=-6c-0,5c²-c²=-1,5c²-6c
c/ (2a-b)(a-2b)+5a²=2a²-4ab-ab+2b²+5a²=7a²-5ab+2b²
d/ (b-4)(b-3)-b(b+3)=b²-7b+12-b²-3b=-10b+12
e/ -(a-b)-5(a-2)(b+1)=-a+b-5(ab+a-2b-2)=-a+b-5ab-5a+10b+10=-6a+11b-5ab+10
f/ x(y+2)+(3x+4-y)(y+4)=xy+2x+3xy+12x+4y+16-y²-4y=-y²+4y+14x+4xy+16
2009-11-27T20:20:02+01:00
A)===k2-0,5lk+6k-3l+k2=2k2-0,5lk+6k-3l
b)(c-1,5c)(12+c)-c2=12c+c2-18c-1,5c2-c2=-1,5c2-6c
c)(2a-b)(a-2b)+5a2=2a2-4ab-ab+2b2+5a2=-5ab+2b2+7a2
d)==b2-3b-4b+12-b2-3b=-10b+12
e)==-a+b-5ab-5a+10b+10=-6a+11b-52b+10
f)==xy+2x+3xy+12x+4y+16-y2-4y= 14x+4xy-y2+16



np 4x2 to znaczy 4x do kwadratu